The Degree of Including Contextual Questions ‎According to the Program for International ‎Student Assessment (PISA) in Science ‎Textbooks for the Intermediate Stage in Saudi ‎Arabia - Al-Rosaa, Tahany (Jordan Journal of Educational Sciences, 2023)
The main goal of this study was to ascertain how much contextual searches and their corresponding domains are present in Saudi Arabian science textbooks for the intermediate level. The sample consists of questions from intermediate-level science textbooks. The researcher created an analytic tool that comprised the type of context and the contextual question domains in order to meet the study objectives. The question was regarded as a unit of analysis, and there were 1,857 questions examined. Frequencies and percentages were used in the statistical treatment. The results revealed a 5.6% decline in the percentage of contextual questions in scientific textbooks, a 6.8% increase in concealed questions, and an 88% increase in conceptual questions. The personal domain was the most often asked contextual question (76%). The percentage of global domain queries reached 16%, while the percentage of local domain questions fell to 8%.